Women in the New Testament world - Hylen, Susan E. (Essentials of biblical studies, 2018)
This text presents and interprets evidence for women's lives in the social context of the New Testament. Some of the evidence from this period of Roman history suggests that women's roles were sharply restricted. Other evidence shows women taking on leadership roles, managing property, and the like. Previous interpreters have often argued that the two kinds of evidence describe different groups or arenas where women's activity was either forbidden or allowed. However, this work argues that the evidence points to complex gender norms that were sometimes in tension